Interactions between faunal community and decomposition processes in relation to microclimate and heterogeneity in boreal forest soil - Sulkava, Pekka (2001)
The aim of this thesis was to assess the effects of soil spatial heterogeneity and microclimatic conditions on the decomposer community structure, biotic interactions within the community and soil processes mediated by the community. Several experiments were carried out in laboratory microcosms and in the field. The microcosms were constructed using coniferous forest soil materials. They were incubated at different moistures and temperatures and they contained different food webs of soil organisms, depending on the aims of the experiment. In two experiments, microcosms contained humus and four different litter materials, either separately in four patches or mixed with each other in one patch. In the field experiment, snow-covered forest soil was compared with roof-covered test plots in which snow did not protect the soil against frost. Microclimatic conditions, decomposer community structure and soil processes were connected by complex interactions. Enchytraeid biomass and N-mineralisation were closely correlated in coniferous forest soil, and a diverse community of microarthropods affected N-mineralisation only indirectly by regulating the enchytraeid populations at low and medium moistures. Hard frost disturbance on snowfree field plots and in microcosms decreased heavily the biomass of enchytraeids and the abundance and species richness of microarthropods. However, recovery of populations was fast and any effects on N-mineralisation remained temporary. Patchy soil structure maintained the species richness of microarthropods. Moreover, the effect of soil fauna on decomposition processes was more prominent in microcosms with one patch than in four patches. In the microcosms with plants, the increasing effect of soil fauna on carbon assimilation apparently compensated their stimulating effect on soil respiration, observed in the experiment without plants. Carbon dynamics, plant growth and fauna! diversity were similar independently of the patch treatment at the end of the experiment, suggesting that the impacts of initial heterogeneity do not persist in the long run.